Assessment of organics and nitrogen removal of aerobic granular sludge with the alternating operation of oxic – anoxic – oxic phases and different feeding mode in sequential batch reactor - Tran, Quang Loc; Thi Tu, Tran; Dang Hai, Nguyen; Quang Hung, Nguyen; Thanh Kien, Dinh (Creative Science, 2021)
Organic matters and nitrogen removal efficiencies from industrial wastewater were evaluated by the aerobic granular sludge (AGS) process with the alternative oxic/anoxic conditions and different feeding regime in Sequencing Batch Reactor (SBR). The experiment was carried out in two lab-scale SBR (R1 and R2) with the same alternation of oxic-anoxic-oxic (O-A-O). Specifically, R1 was applied for one-step feeding at the beginning of each cycle and R2 for two-step feeding with one more filling in anoxic phase. Our study results showed that AGS remained stable and maintained excellent settling properties with low SVI of 42 – 45 mL gTSS–1, and high sludge biomass of 7.46 – 7.53 g L–1 was retained in both reactors. Specific Oxygen Uptake Rate (SOUR) was 80.70 and 87.90 mgO2 gTSS–1 h–1 in R1 and R2 respectively that indicated the high biological activity of granular sludge. The high biomass retained and bioactivity of the organism in sludge leads to stable COD removal efficiency in both reactors about 88 – 91% during the experiment. In additional, total nitrogen (TN) removal efficiency of R2 (80.20 – 85.60%) was 13 – 15% higher than that of R1 (68.42 – 71.20%). Our study concluded that nitrogen removal via nitrification and denitrification was achieved in SBR operation with alternating of O-A-O, and two-step feeding was appropriated proposal for organic matters and nitrogen removal in single reactor. And step-feeding was an effective option in providing internal carbon source from wastewater as electron donor for denitrification in the anoxic phase instead of using external carbon source in SBR operation.